"The rules of the game": how to favor entrepreneurship and creativity in a non-capitalistic economy - Labégorre, Quentin (2016)
The economy, nowadays, is leading us toward a huge crisis. An environmental crisis, a new financial crisis and finally a war crisis. The aim of this paper is to propose a way to change our economy to favor a better perspective of the future. In order to promote this new economy, two suggestions are proposed: promote entrepreneurship and promote creativity within an economy that would aim at getting full employment and at avoiding any unethical action towards the environment. Several propositions are made about education, culture and economy to obtain sustainable changes in the economic landscape and in order to promote entrepreneurship in this fictive economy.